KARAKTERISTIK KONDISI LINGKUNGAN PENDERITA MALARIA TERHADAP KEJADIAN MALARIA - Aditya Andra Perdana (Jurnal Medika Hutama, 2021)
Malaria is the fifth leading cause of death from infectious diseases in the world, according to the World Health Organization (WHO) there are 3.3 billion people living in areas at risk of malaria transmission. Half of Indonesia's population lives in malaria endemic areas. Malaria is an infectious disease caused by sporozoa of the genus Plasmodium which consists of species Plasmodium vivax, Plasmodium malariae, Plasmodium falciparum, and Plasmodium ovale which enter the body through the bite of a female Anopheles mosquito. The environment in the house that plays an important role in the frequency of contact of mosquito bites to humans such as the condition of the walls of the house, the installation of wire netting on the ventilation, lighting, ceiling of the house and hanging clothes.